2019
DOI: 10.1093/nar/gkz674
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing whole genome bisulfite sequencing data from highly divergent genotypes

Abstract: In the study of DNA methylation, genetic variation between species, strains or individuals can result in CpG sites that are exclusive to a subset of samples, and insertions and deletions can rearrange the spatial distribution of CpGs. How to account for this variation in an analysis of the interplay between sequence variation and DNA methylation is not well understood, especially when the number of CpG differences between samples is large. Here, we use whole-genome bisulfite sequencing data on two highly diver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…We here generated the single‐base‐resolution DNA methylation map of tea plants under chilling stress through whole‐genome bisulfite sequencing. The average bisulfite non‐conversion rate is approximately 0.3% in our samples, which is comparable with previous studies (Li et al, 2020; Wulfridge et al, 2019). Approximately 21, 23 and 56% of the cytosines in the tea plant genome are methylated at CG, CHG and CHH sites, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…We here generated the single‐base‐resolution DNA methylation map of tea plants under chilling stress through whole‐genome bisulfite sequencing. The average bisulfite non‐conversion rate is approximately 0.3% in our samples, which is comparable with previous studies (Li et al, 2020; Wulfridge et al, 2019). Approximately 21, 23 and 56% of the cytosines in the tea plant genome are methylated at CG, CHG and CHH sites, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…It was previously reported that the genomic variations, including single nucleotide variants, insertions, and deletions, would introduce “quantification bias” of methylation levels in the step of alignment for BS-seq reads ( 31 ). For example, if a sample genome has a “CG-to-TG” variant relative to the reference genome sequence, standard alignment approaches would consider a “TG” dinucleotide in a read to be derived from an unmethylated CpG dinucleotide, resulting in an underestimation of methylation level ( 31 ). Such a quantification bias would lead to inaccurate data interpretation when comparing methylation patterns between species and human normal-cancer datasets with divergent genotypes ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if a sample genome has a “CG-to-TG” variant relative to the reference genome sequence, standard alignment approaches would consider a “TG” dinucleotide in a read to be derived from an unmethylated CpG dinucleotide, resulting in an underestimation of methylation level ( 31 ). Such a quantification bias would lead to inaccurate data interpretation when comparing methylation patterns between species and human normal-cancer datasets with divergent genotypes ( 31 ). In addition to a dedicated bioinformatics approach for mitigating the quantification bias ( 31 ), the HK model presented in this study would provide an opportunity to address the quantification bias due to the issue of mappability in the standard alignment approaches for BS-seq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This acts as a confounding factor in downstream analysis, including finding differentially methylated regions. The conversion efficiency can be directly derived from unmethylated lambda DNA spiked in by calculating the fraction of converted bases at cytosine sites or using available software programs [37,77,78].…”
Section: Data Quality Assessmentmentioning
confidence: 99%